PARALINGUTIC TOOLS IN MEDIA-COMMUNICATIVE COMMUNICATION (Scientific journal of the Fergana State University, 2026)
This article analyzes the importance of paralinguistic tools in media-communicative communication and their linguocultural research. Paralinguistic tools are considered as the main element that complements and sometimes replaces verbal tools in communication. In the study, the linguistic and cultural and linguistic psychological dimensions, gender characteristics, national and professional aspects of non-verbal tools, as well as their importance in society and professional activities were analyzed. Universal and special types of paralinguistic tools are described as an important factor in increasing the effectiveness of communication.